Synthesis and radiolabeling of 64Cu-labeled 2-nitroimidazole derivative 64Cu-BMS2P2 for hypoxia imaging. Issue 5 (1st March 2016) - Luo, Zheng; Zhu, Hua; Lin, Xinfeng; Chu, Taiwei; Luo, Ruyi; Wang, Yunhua; Yang, Zhi
Graphical abstract: Abstract: The objective of this study was to develop a positron emission tomography (PET) probe with hypoxia targeting specificity and a relatively long half-life. The synthesis, 64 Cu-labeling in vitro and in vivo study of the novel 2-nitroimidazole complex 64 Cu-BMS2P2 is presented in this study. The hypoxia targeting capacity of 64 Cu-BMS2P2 in vitro was evaluated and compared with the 64 Cu-BMS181321, and confirmed by PET imaging in vivo and immunohistochemistry for carbonic anhydrase 9 (CA9) in a tumor mouse model. These results suggest that 64 Cu-BMS2P2 is a promising candidate for PET hypoxia imaging and worthy of further investigations in dynamic hypoxia imaging.